2019
DOI: 10.24018/ejece.2019.3.6.154
|View full text |Cite
|
Sign up to set email alerts
|

System for Nature-inspired Signal Processing: Principles and Practice

Abstract: This paper establishes the foundational principles and practice for a unified theory of arbitrary information management by disclosing systems, devices and methods for the management of substrates or biological substrates. In this context, a substrate is any aspect of any entity that is capable of responding to or emitting stimuli irrespective of whether the stimuli actually emanate from any aspect of the entity or not. Management of substrates could be achieved through the management of stimuli that modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 49 publications
8
9
0
Order By: Relevance
“…Recent work by Zhang et al 24 permits the direct imaging of signals propagating through myelinated axons and demonstrates conclusively that electrical signals propagate through different neurons at finite, measurable and disparate speeds and consequently are likely to be detected at different layers of neuronal populations at different times. This is direct confirmation of PREDICTION I made by Ekpar 22,23 on the basis of our framework and reproduced here with an expanded description of the distribution of signals.…”
Section: Prediction IIIsupporting
confidence: 89%
See 4 more Smart Citations
“…Recent work by Zhang et al 24 permits the direct imaging of signals propagating through myelinated axons and demonstrates conclusively that electrical signals propagate through different neurons at finite, measurable and disparate speeds and consequently are likely to be detected at different layers of neuronal populations at different times. This is direct confirmation of PREDICTION I made by Ekpar 22,23 on the basis of our framework and reproduced here with an expanded description of the distribution of signals.…”
Section: Prediction IIIsupporting
confidence: 89%
“…Zhang et al 24 recently demonstrated the direct imaging of signals propagating through myelinated axons while Seeber et al 25 provided direct evidence that scalp EEG recordings can detect subcortical electrophysiological activity. These results confirm the correctness of the principles underpinning the conceptual framework on which our work is based and confirm all three related predictions reported by Ekpar 22,23 with far-reaching implications.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations